ASOSIASI HbA1c DENGAN HASIL TES SKRINING TB-PARU PADA PASIEN DI RSUD BUDHI ASIH JAKARTA TAHUN 2022 - Setiawan, Heru; Herietrenggi, Kristanti; Octaviani, Azzya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
Pulmonary TB is still a poor record of direct infectious disease control in Indonesia and even the world. The lack of HbA1c testing in TB patients has delayed early detection of TB-DM. Poor diabetes control can prolong the duration of TB treatment. Longer disease duration can lead to complications. The highest number of TB cases in DKI Jakarta is in the East Jakarta area, Budhi Asih Hospital conducts TB screening examinations for community coverage in East Jakarta. This study aims to determine the association of HbA1c with the results of the Lung TB screening test in patients at RSUD Budhi Asih Jakarta in 2022. The method used was descriptive analytic observational with a cross sectional design carried out in the medical records and laboratories of RSUD Budhi Asih Jakarta in February-June 2023 with 100 patient data. The results of the negative TB group were found in the controlled DM group, while the positive TB results were dominated by the uncontrolled DM group with the results of chi-square analysis there was a significant association between HbA1c results and the results of the Lung TB screening test in patients at RSUD Budhi Asih Jakarta in 2022 (p = 0.036) with Odds Ratio = 2.667. From this study, it is expected that it is important for screening patients and diagnosed with Lung TB to control glycemic levels by routinely checking HbA1c levels.